Effect of fertility levels and biofertilizers on agrophysiological performance, productivity and quality of chickpea (Cicer arietinum) - VERMA, GAURAV; YADAV, DEEN DAYAL; SHARMA, V K; KUMAR, AMIT; SINGH, RAMESH KUMAR; UPADHYAY, PRAVIN KUMAR; GUPTA, GAURENDRA (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted during winter (rabi) of 2016–17 at the Students' Instructional Farm of Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh to evaluate the effect of different fertility levels and biofertilizers on agrophysiological performance, productivity and quality of late sown chickpea (Cicer arietinum L.). The experiment comprised of 12 treatment combinations in split plot design which comprised 4 treatments [F1 (control), F2 (RDF 100%), F3 (75% RDF), F4 (50% RDF)] in main plot and 3 treatments [B1 (Rhizobium + PSB), B2 (Rhizobium + PGPR) and B3 (Rhizobium + PSB + PGPR)] in sub plots with three replications. Results showed that among the different fertility levels, application of 100% RDF significantly enhanced agrophysiological performance, yield attributes, yield, and protein yield over the control. Among the different biofertilizers treatments application of Rhizobium + PSB + PGPR had significantly improved agrophysiological performance, yield attributes, seed yield and protein yield as compared to Rhizobium + PGPR. The combined application of 100% RDF with Rhizobium + PSB + PGPR resulted in significantly higher seed yield of late sown chickpea during winter (rabi).